A lattice Monte Carlo analysis on thermal diffusion in syntactic hollow-sphere structures - Farnsworth, J. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2010)
The Lattice Monte Carlo method [1] is a computationally intensive approach towards the study of thermal material properties. The Lattice Monte Carlo method has previously been used in the area of mass diffusion, and has more recently been applied towards the analysis of thermal diffusion in materials. Whilst previous studies have focused on two-phase material consisting of component material and pore geometry only, this study applies the Lattice Monte Carlo method towards the investigation of three-phase Metallic Hollow Sphere Structures (MHSS). MHSS consist of high-conducting metallic shells, low-conducting adhesive and non-conducting pores. In the present study, three-dimensional computerised models of the MHSS are built up from analysis of computed tomography (CT) scans. The results of this numerical analysis indicate a spatial variation of the thermal conductivity. However, MHSS can be considered as being isotropic to a good approximation.